2017
DOI: 10.4038/jrrisl.v94i0.1821
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous nitric oxide donor sodium nitroprusside ameliorates root architecture and growth performance in young budding polybagged plants of rubber (<em>Hevea brasiliensis</em>)

Abstract: Shoot die back condition has been observed in young budding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…In addition, it is accepted that high NO donor concentrations may induce detoxification responses while lower concentrations might more accurately reflect its role as a signalling molecule (Wink and Mitchel, 1998;Beligni and Lamattina, 1999). Nayanakantha et al (2014) demonstrated that application of 50ml of SNP (at 50-500μM) into polybagged rubber seedlings greatly improved the root and growth characteristics under glass house conditions.…”
Section: Growing Of Rubber Seedlingsmentioning
confidence: 99%
“…In addition, it is accepted that high NO donor concentrations may induce detoxification responses while lower concentrations might more accurately reflect its role as a signalling molecule (Wink and Mitchel, 1998;Beligni and Lamattina, 1999). Nayanakantha et al (2014) demonstrated that application of 50ml of SNP (at 50-500μM) into polybagged rubber seedlings greatly improved the root and growth characteristics under glass house conditions.…”
Section: Growing Of Rubber Seedlingsmentioning
confidence: 99%
“…Sphagnaticola species have antimicrobial, insecticidal, larvicidal and trypanosomicidal properties and are used for medicinal purposes (Huang et al 2006;Maldini et al 2009;Toppo et al 2013) and as a decorative ground cover in many parts of the world (Wagner et al 1990;Macanawai 2013). It is also used as a cover crop in rubber and tea plantations to control soil erosion in Asia (Nayanakantha 2007). Furthermore, it is used for ground cover in Middle Eastern countries, which helps stabilize the soil and prevent it from moving due to wind.…”
Section: Introductionmentioning
confidence: 99%